Shame and the captives [large type] : a novel - Keneally, Thomas (Thorndike Press, 2015)
Inspired by a notorious incident in New South Wales in 1944, this beautifully rendered novel from the author of Schindler's List and The Daughters of Mars explores events at a World War II prison camp where Japanese prisoners resolve to take drastic action to wipe away their shame. This profoundly gripping and thought-provoking novel once again shows Keneally as a master at exploring ordinary lives caught up in extraordinary events.